Our champions! - Noor Azlan, Ratin; Jamiaah, Noor Rahmad (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
20 April 2010. From 22 February to 5 March this year, UMP had organised its inter-faculty sports carnival to foster greater sporting spirits among its staff and also to form teams to represent UMP in SUKUM 2010 in USM Penang.